The Changes of KCNQ5 Expression and Potassium Microenvironment in the Retina of Myopic Guinea Pigs - Yang, Qin; Tan, Qing Qing; Lan, Chang Jun; Lv, Bo Zhen; Zhou, Gui Mei; Zhong, Wei Qi; Gu, Zhi Ming; Mao, Yu Mei; Liao, Xuan (Frontiers in Physiology, 2021)
KCNQ5 is suggestively associated with myopia, but its specific role in the myopic process has not been studied further. The aim of this study was to investigate the expression of potassium channel gene KCNQ5 and the changes of K+ microenvironment within the retina of form deprivation myopia (FDM) guinea pigs. A total of 60 guinea pigs were randomly divided into the normal control (NC) group, the self-control (SC) group, and the form-deprivation (FD) group for different treatments. Molecular assays and immunohistochemistry (IHC) were conducted to measure the expression and distribution of KCNQ5-related gene and protein in the retina. We determined the K+ concentration in the retina. In addition, the possible effects of form deprivation on potassium ionic currents and the pharmacological sensitivity of KCNQ5 activator Retigabine and inhibitor XE991 to the M-current in RPE cells were investigated using the patch-clamp technique. As a result, FD eyes exhibited more myopic refraction and longer AL. The mRNA and protein levels of KCNQ5 significantly decreased in the FD eyes, but the K+ concentration increased. In addition, the M-type K+ current [IK(M)] density decreased in FD RPE cells, and were activated or inhibited in a concentration-dependent manner due to the addition of Retigabine or XE991. Overall, KCNQ5 was significantly downregulated in the retina of FD guinea pigs, which may be associated with the increasing K+ concentration, decreasing IK(M) density, and elongating ocular axis. It suggested that KCNQ5 may play a role in the process of myopia, and the intervention of potassium channels may contribute to the prevention and control of myopia.